A 4‐minute solution for submillimeter whole‐brain T1ρ quantification. Issue 6 (9th January 2021) - Zhu, Yanjie; Liu, Yuanyuan; Ying, Leslie; Qiu, Zhilang; Liu, Qiegen; Jia, Sen; Wang, Haifeng; Peng, Xi; Liu, Xin; Zheng, Hairong; Liang, Dong
Abstract : Purpose: To develop a robust, accurate, and accelerated T1ρ quantification solution for submillimeter in vivo whole‐brain imaging. Methods: A multislice T1ρ mapping solution (MS‐T1ρ ) was developed based on a two‐acquisition scheme using turbo spin echo with RF cycling to allow for whole‐brain coverage with 0.8‐mm in‐plane resolution. A compressed sensing–based fast imaging method, SCOPE, was used to accelerate the MS‐T1ρ acquisition time to a total scan time of 3 minutes 31 seconds. A phantom experiment was conducted to assess the accuracy of MS‐T1ρ by comparing the T1ρ value obtained using MS‐T1ρ with the reference value obtained using the standard single‐slice T1ρ mapping method. In vivo scans of 13 volunteers were acquired prospectively to validate the robustness of MS‐T1ρ . Results: In the phantom study, the T1ρ values obtained with MS‐T1ρ were in good agreement with the reference T1ρ values ( R 2 = 0.9991) and showed high consistency throughout all slices (coefficient of variation = 2.2 ± 2.43%). In the in vivo experiments, T1ρ maps were successfully acquired for all volunteers with no visually noticeable artifacts. There was no significant difference in T1ρ values between MS‐T1ρ acquisitions and fully sampled acquisitions for all brain tissues ( p ‐value > .05). In the intraclass correlation coefficient and Bland‐Altman analyses, the accelerated T1ρ measurements show moderate to good agreement to the fully sampled reference values. Conclusion: The proposed MS‐T1ρ solution allows for high‐resolution whole‐brain T1ρ mapping within 4 minutes and may provide a potential tool for investigating neural diseases.